Mapping Transformation: Lessons Learned from Poso District's Post-Conflict Deradicalization - Hasrullah Hasrullah; Nosakros Arya (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The Post-Conflict Poso Deradicalization Program was launched after a series of conflicts between religious groups in Poso, Central Sulawesi, Indonesia, have been ongoing since 1998. The main objective of this program is to alleviate tensions among these groups and promote peace and reconciliation in the region. In this context, the perspective of communication science plays a crucial role in bridging the perceptual gaps that exist between the community and the Poso government. Through this research, the researcher describes and analyzes the communication network structure and the roles of actors in seeking information about the deradicalization program. This communication network research adopts a descriptive approach. Primary data was collected through interviews with actors involved in the deradicalization program. The data was then coded based on the frequency of communication among the actors. The processing and visualization of the communication network were conducted using UCINET.The research finds that the formed communication networks indicate a relatively optimal level of communication, especially among the implementing groups and participants of the deradicalization program. In the post-conflict Poso deradicalization program, both Islamic and Christian sides have influential figures who can serve as role models for the community in eradicating the seeds of conflict that can always resurface.